Non linear probabilistic analysis of reinforced concrete structures - Matos, José C. (2010)
The behaviour of reinforced concrete bridges is doted of uncertainty as main parameters, like the ones related to material properties, are variable and not deterministic. In order to take this into consideration, a non linear probabilistic analysis should be developed. This paper presents an application of it on the evaluation of the structural behaviour of two batches of reinforced concrete beams, which were loaded, in laboratory, up to failure. However, when performing it, a previous attention must be paid to the intervenient parameters. In fact, on the one hand it is important to consider the highest number of parameters as possible but, on the other hand, this implies higher computational costs. In order to avoid this, it is essential to identify, by developing a sensitivity analysis, all critical parameters. A comparison of numerical results with obtained experimental data is executed, being, the advantages of such kind of analysis, pointed out.